Parâmetros de estudo em vazão de projeto para renovação de outorga de barramento. - Yogi, Fernando (2018)
One of the tools that works in favor of the balanced distribution of waters and mediating conflicts is the granting of use of water resources, with which they are issued through analysis of hydrological studies. For this aspect, the grant is an administrative tool that acts in the concession of the environmental matter "water", and from time to time need to be renewed. An application for renewal of concession in the State of São Paulo for hydraulic detention works, such as the buses, needs to present the estimates of the runoff with parameters that may be associated to land use and occupation. Thus, it is fundamental to apply rain-flow models that represent the phases of the hydrological cycle, are simplified but do not lose their essence and good power of response. The waterproofing processes in expansion in the urban centers provide an increase in the surface runoff and changes in the estimates obtained by the rainfall-flow models, resulting in the reduction of infiltration and the decrease of the natural damping capacity of the river watersheds. In this way, the objective of this work was to associate land uses in the sub watershed of River of Suru in the municipality of Santana de Parnaíba, correlating them with rainfall-flow models, incorporating studies for grant renewal. River of Suru is a water body that is present in a region that contrasts urban and rural. It presents different uses and occupations and contributes in this way to the association of elements of the terrestrial coverage with rainfall-flow models. Among the baseline methodologies used for correlation are the I-Pai-Wu method and the Soil Conservation Service (SCS). The first one, through its classes, presented a good adaptation to more denser areas, while the second one, SCS, stands out for a good correlation with watershed with vegetated characteristics. In the method, geoprocessing techniques were applied in obtaining terrestrial coverage parameters (Curve Number - CN / Runoff Coefficient) in orthorectified aerial images with spatial resolution of 1 m, with an object - based classification and manual classification in the sub watershed of River of Suru, with an area of approximately 21 Km2. The survey made for the use and occupation of land was carried out by two different methods to simulate the values Lof surface runoff. The parameters of the I-Pai-Wu and Soil Conservation Service methods were followed by a manual classification aided by classification keys, and object-based classification based on set theory and fuzzy logic. Precipitation was calculated according to the most representative rainfall equation for the region. With the possession of hydrological data and the use and occupation of land, it was possible to calculate the project flow. The simulations performed in this study demonstrated that land use and land use in these two methods can correlate parameters for rainfall-flow models for flow calculation, integrating the hydrological studies of the granting and renewal processes.